Efficiency Of Microfinance Institutions And Economic Freedom Nexus: Empirical Evidence From Four Selected Asian Countries - Fakarudin Kamarudin; Fengsheng Chien; Hafezali Iqbal Hussain; Muhammad Sadiq; Nazratul Aina Mohamad Anwar (Vilnius University, Lithuania, 2024)
The impact of economic freedom’s dimensions specifically on law’s rule and government’s size to the efficiency of the financial and social efficiency of the microfinance institutions (MFI) have been examined in this study. This study comprises of total 165 MFIs from four selected Asian countries over the period from 2011 to 2019. In overall, the MFIs are more capable to generating revenue from their financial activities to ensure their sustainability and to ensure they manage to provide better financial inclusions to the lower income society rather than merely focus on minimizing the poverty. The results from the panel regression analysis implied that property rights, government spending and tax burden are negatively significant with social efficiency of MFIs. On the other hand, government integrity showed a significant and positive relationship with social efficiency of MFIs. However, these variables revealed a consistent negative but insignificant relationship with the financial efficiency of MFIs.